131 Student-led reflective practice course for leadership in medical education. (16th November 2020) - Shenoy, Riddhi; Abdall-Razak, Ali; Singh, Harmanjit
Abstract : Medical students are required by the General Medical Council to reflect on their practice but few opportunities are presented for group-based reflection at medical school. A two-session near-peer led reflective practice course was created for intercalating medical students undertaking group coursework. The first session involved a group discussion of one student's team experience to analyse causative factors for the feelings and behaviours of individual members that weaken group response to challenges. Students also discussed their existing reflective practice and created their own course learning objectives to foster commitment. The second observed session consisted of students conducting their own reflective exercise to their peers. From the discussions, students most frequently reported a reluctance to assign leadership roles in peer groups, as it was discordant with the ingrained group social dynamic. Following the course, students were much more willing to generate an action plan to approach challenging team members for an honest and collaborative conversation. Student feedback emphasised the value of near-peer observation in encouraging information sharing with the group and discouraging relapse into counter-productive discussion and blaming. Following the course, students also reported using increased and broader opportunities for reflection and this was unrelated to the outcome of the situation. These findings show students are an untapped resource for developing better, sustainable and more accessible reflective practice in medical education. It suggests the value of near-peers as role models to favourably cast the active pursuit of reflection, thereby increasing student internalisation of group reflection. Student-led reflective groups may address important gaps in the development of leadership skills in medical education. These skills have utmost relevance in training students to become part of the clinical workforce and improving patient safety.